High entropy alloys as a bold step forward in alloy development - D. B. Miracle (Nature Portfolio, 2019)
Diluting a base element with small amounts of another has served as the basis for developing alloys for thousands of years since the advent of bronze. Today, a fundamentally new idea where alloys have no single dominant element is giving new traction to materials discovery.